The determinants of external debt in ASEAN / Muhammad Sufi Zahid - Zahid, Muhammad Sufi (2017)
In Southeast Asia, debt problem still the most arising issues every year. Most of the country's perform external debt is a country that suffers from shortfall of domestic savings and country must achieve the objectives of national development in foreign exchange. The aim of this study is to analyze the determinants that affecting the external debt in Asean. In this study, the Regression Model which are Pooled Ordinary Least Square (POLS), Random Effect Model (REM), and Fixed Effect Model (EFM) are used to test the relationship between the dependent and independent variables by using panel data for the period 1986 to 2015. The empirical analysis reveals that the independent variables for economic growth, government expenditure, and saving has significant relationship towards the dependent variable of external debt, while there is no significant relationship between exchange rate on external debt. As a conclusion, this study is important in understanding how these independent variables influence the external debt.